2017
DOI: 10.1007/s12306-017-0492-x
|View full text |Cite
|
Sign up to set email alerts
|

Radial head prosthesis: results overview

Abstract: Background/purposeRadial head replacement is frequently used in treatment of radial head fractures or sequela. Impossibility to restore a correct anatomy, acute elbow traumatic instability and failure of osteosynthesis hardware are the most common indications. The authors describe their case studies and results on the implantation of various radial head prostheses.MaterialsBetween June 2005 and June 2016, 28 radial head prostheses were implanted in the same number of patients with an average follow-up of 49 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This suggest that the use of prostheses, if well positioned and selected, is a valid solution in the treatment of complex fractures of the radial head with poor prognosis. Good results in the reduction of pain, recovery of movement, and improved quality of life were shown [ 4 , 6 ]. This result is supposedly limited in time, as shown in our case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggest that the use of prostheses, if well positioned and selected, is a valid solution in the treatment of complex fractures of the radial head with poor prognosis. Good results in the reduction of pain, recovery of movement, and improved quality of life were shown [ 4 , 6 ]. This result is supposedly limited in time, as shown in our case report.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy can include osteosynthetic treatment, resection of the entire radial head, or implantation of a radial head prosthesis [ 1 3 ]. There are various implants for the latter [ 4 ]. A study by Maghen et al showed no complications in a follow-up period of an average of five years after implantation of silastic radial head prostheses, with simultaneous surgical restoration of the ligamentous apparatus of the elbow [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For most of authors, mid term follow-up has shown satisfactory results in range of motion recovery (average flexion-extension arc of motion: 116°). Good results in DASH scores (from 7 to 24) and MEPS scores (from 79 to 100) and low VAS pain evaluation scale (from 0 to 2.2) are reported [ 13 – 32 ]. A certain loss of grip strength compared to contralateral side is often described (average loss of strength: 10% respect to the contralateral side).…”
Section: Discussionmentioning
confidence: 99%
“…Rh prosthetic replacement (RhR) is indicated for comminuted Rh fractures in association with other elbow fractures, with lesions of the interosseous membrane or with elbow instability [2][3][4][5]. This surgical treatment can provide satisfactory results at long-term follow-up [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%